الرقابة الشرعية ودورها في تقويم الأداء الشرعي للمصارف الإسلامية العاملة في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2016)
قامت المصارف الإسلامية باعتبارها البديل الشرعي للمصارف التقليدية, ولهذا يعدّ وجود رقابة شرعية أمراً ضرورياً للمصارف الإسلامية. وتعود أهمية الرقابة الشرعية إلى دورها في بيان الأحكام الشرعية للمعاملات المصرفية, والتأكد من مدى التزام المصرف بها, بما يضمن إجراء المعاملات كافة ،وفق أحكام الشريعة الإسلامية, و يضمن سلامة ومصداقية المصارف الإسلامية. انطلاقاً من هذه الأهمية يتناول هذا البحث الرقابة الشرعية على المصارف الإسلامية ودورها في تقويم الأداء من الناحية الشرعية. حيث تمَّ التعريف بمفهوم الرقابة الشرعية، هيكلتها، مراحلها, ومشكلاتها, ثم تمَّ تقييم هيئات الرقابة الشرعية ودورها في ضبط الأداء الشرعي للمصارف الإسلامية العاملة في سورية باستخدام مجموعة من المعايير الملائمة. بعد ذلك تمَّ التوصل إلى مجموعة من الاستنتاجات والتوصيات. ومن أهم الاستنتاجات أنَّ هيئة الرقابة الشرعية في المصارف الإسلامية العاملة في سورية تمتلك الكثيرد من المقومات التي تمكنها من أداء دورها في ضبط وتقويم عمل المصارف الإسلامية من الناحية الشرعية. وذلك من خلال شكل وتكوين الهيئة, وتمتعها بدرجة مقبولة من الاستقلال الإداري والمالي, ومن خلال إلزامية قراراتها, وطبيعة المهام الموكلة إليها. وبهذا يعدّ وضع هيئات الرقابة الشرعية في المصارف الإسلامية العاملة في سورية منسجماً إلى حدٍ كبير مع هدفها في ضمان الالتزام التام للمصارف الإسلامية بأحكام الشريعة الإسلامية. ومن أبرز التوصيات التي قدمها البحث ضرورة العمل على تلافي السلبيات والنواقص, وتوفير المزيد من المقومات والمتطلبات اللازمة لتفعيل الرقابة الشرعية على المصارف الإسلامية, وتمكينها من ضبط وتقويم الأداء الشرعي للمصارف على أكمل وجه. Islamic banks were created as an Islamic alternative to traditional banks. Hence, the existence of legitimate oversight is considered necessary to Islamic banks. The importance of Shari'ah control is related to its role in a legitimate banking provisions, and ensuring the Bank's commitment, to ensure all transactions are in accordance with the Islamic Shari'ah, and thus ensures the integrity and credibility of Islamic banks. From these importance, this research deals with the Shari'ah control in Islamic banking and its role in evaluating the performance according to the Shari'ah. The concept of Shari'ah control, its structure, stages, and problems were studied. Then the Shari'ah control in Syria and its role in adjust the performance of Islamic banks was evaluated by a set of appropriate standards. At the end, the research drew a set of conclusions and recommendations. One of the most important conclusions is that, the Shari'ah control board in Islamic banks in Syria has many features that enable them to perform its role in controlling and evaluating the work of the Islamic banks in terms of Shari'ah. Through the form and composition of the Commission, having a degree of administrative and financial autonomy, mandatory resolutions, and the nature of the tasks entrusted to it. As a result, Shari'ah control boards in Islamic banks in Syria are considered to be in line with their goal of ensuring full adherence to Islamic Shari'ah. One of the most important recommendations is that, working to avoid shortcomings and deficiencies, providing more features and requirements for activation of Shari'ah control, and enabling it to adjust and correct performance of the Islamic banks.